Asymmetric information on the market for energy efficiency: Insights from the credence goods literature - Bruno Lanz; Evert Reins (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
Imperfect information is widely acknowledged to hamper the adoption of energy efficient technologies. In this paper, we study supply-side implications of the associated incentive structure. We build on existing evidence suggesting that energy efficiency owns a credence component, whereby the supply side of the market has more information about what technology is best for consumers. The literature on credence goods markets suggests that informational advantage by an expert-seller leads to market inefficiencies, including low trade volume. We start by developing a simple framework to study supply-side incentives related to the provision of energy efficient technologies. We then document inefficiencies and potential remedies by discussing linkages between an empirical literature on credence goods and that on the market for energy efficiency. Doing so, we identify policy implications and research gaps that are relevant for the adoption of energy efficiency technologies.
Keywords: D18; D82; H23; Q41; 330; Energy efficiency; Asymmetric information; Credence goods; Energy policy; Environmental externalities; Technology adoption